Ultrasonic-assisted, additive-free Pd-catalyzed Suzuki–Miyaura cross-coupling enabled synthesis of novel arylated benzofuran-triazole hybrids - Saif, Muhammad Jawwad; Ahmad, Sajjad; Mushtaq, Aqsa; Munawar, Saba; Zahoor, Ameer Fawad; Ettampola, Shoela; Irfan, Ali; Kotwica-Mojzych, Katarzyna; Ruszel, Karol; Mojzych, Mariusz (Frontiers in Chemistry, 2025)
An additive-free and ultrasound-assisted approach has been established for the Suzuki–Miyaura cross-coupling reaction between substituted boronic acid and benzofuran-endowed aryl halides by employing a catalytic amount of Pd(PPh3)4. The resulting substituted biaryls were then employed as efficient starting materials to furnish a novel library of arylated benzofuran-triazole hybrids 13(a–i). The method offers a facile, efficient, and less time-consuming approach under non-inert conditions to synthesize the targeted derivatives in a good to excellent yield range of 70%–92%.